2011 Fifth International Conference on Innovative Mobile and Internet Services in Ubiquitous Computing 2011
DOI: 10.1109/imis.2011.88
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Driven Policy Enforcement through Gate Automata

Abstract: Abstract-In this paper we introduce the notion of gate automata for describing security policies. This new kind of automata aim at defining a model for the specification of both security and trust policies.The main novelty of our proposal is a unified framework for the integration of security enforcement and trust monitoring. Indeed, gate automata watch the execution of a target program, possibly modifying its behaviour, and produce a feedback for the trust management system. The level of trust changes the env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…We can observe that gate automata extend the automata of [16] in two ways: (i) they can add and remove actions from the target's execution trace (rather than simply halt it) and (ii) they also use special actions for the trust management. For this reason, in [8] we showed that gate automata can be encoded using edit automata [13]. Gate automata differ from edit automata mainly because they manage trust.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…We can observe that gate automata extend the automata of [16] in two ways: (i) they can add and remove actions from the target's execution trace (rather than simply halt it) and (ii) they also use special actions for the trust management. For this reason, in [8] we showed that gate automata can be encoded using edit automata [13]. Gate automata differ from edit automata mainly because they manage trust.…”
Section: Related Workmentioning
confidence: 99%
“…In this paper we show an implementation of the S×C×T framework run-time support using gate automata. We advocate gate automata as a unique formalism for dealing with security and trust [8]. In particular, we show how they can be used for encoding both applications' contracts and security policies in the S×C×T implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation